Absolute quantification of cohesin, CTCF and their regulators in human cells - Holzmann, Johann; Politi, Antonio Z; Nagasaka, Kota; Hantsche-Grininger, Merle; Walther, Nike; Koch, Birgit; Fuchs, Johannes; Dürnberger, Gerhard; Tang, Wen; Ladurner, Rene; Stocsits, Roman R; Busslinger, Georg A; et al. (eLife, 2019)
The organisation of mammalian genomes into loops and topologically associating domains (TADs) contributes to chromatin structure, gene expression and recombination. TADs and many loops are formed by cohesin and positioned by CTCF. In proliferating cells, cohesin also mediates sister chromatid cohesion, which is essential for chromosome segregation. Current models of chromatin folding and cohesion are based on assumptions of how many cohesin and CTCF molecules organise the genome. Here we have measured absolute copy numbers and dynamics of cohesin, CTCF, NIPBL, WAPL and sororin by mass spectrometry, fluorescence-correlation spectroscopy and fluorescence recovery after photobleaching in HeLa cells. In G1-phase, there are ~250,000 nuclear cohesin complexes, of which ~ 160,000 are chromatin-bound. Comparison with chromatin immunoprecipitation-sequencing data implies that some genomic cohesin and CTCF enrichment sites are unoccupied in single cells at any one time. We discuss the implications of these findings for how cohesin can contribute to genome organisation and cohesion.